Thermodynamic modelling of mixtures of water, carbon dioxide and hydrogen at high pressure and temperature for hydrothermal CO2 reduction processes - Navarro-Cárdenas, Iván; Martín, Ángel (Frontiers in Physics, 2023)
In the context of the increasing CO2 emissions and the corresponding environmental problems, CO2 utilization processes that transform CO2 into valuable compounds rather than just capturing and storing it can contribute to the transition to a carbon-free economy, giving value to unavoidable CO2 emissions. Among the different technologies studied, hydrothermal conversion stands out by the high yields achieved in comparatively short reaction times and by the possibility to scale-up the process. The hydrothermal conversion uses CO2 dissolved in aqueous solutions as feedstock, in which bicarbonate is the reacting species. Therefore, knowledge of the equilibrium concentrations of dissolved species is of interest for the development of the process. In this work, a thermodynamic model based on the activity coefficient model developed by Pitzer, Sun & Duan model is implemented and solved. The influence of different process conditions: temperature, pressure, composition of the initial solution, on the equilibrium composition of the dissolution is analyzed with the model. Experimental results obtained in hydrothermal reduction experiments are thus interpreted with the aid of the model. It is observed that the process is favored by moderate temperatures (<500 K), high initial concentrations of sodium bicarbonate (up to 2 mol/kg) and moderate initial concentrations of sodium hydroxide (below 1.5 mol/kg).